Part-time or full-time teleworking? A systematic review of the psychosocial risk factors of telework from home - Antunes, Evelise Dias; Bridi, Leonardo Rodrigues Thomaz; Santos, Marta; Fischer, Frida Marina (Frontiers in Psychology, 2023)
Introduction Since the start of the COVID-19 pandemic thousands of people have experienced teleworking and this practice is becoming increasingly commonplace. This review aims to highlight the differences in exposure to psychosocial risk factors for health between part-time and full-time teleworking from home. Methods The protocol of the systematic review of the literature was registered on PROSPERO 2020 platform according to the PRISMA statement guidelines. The key words “telework” and “frequency” (“part-time” or “full-time”), together with their synonyms and variations, were searched. Independent researchers conducted the systematic search of 7 databases: Scopus, SciELO, PePSIC; PsycInfo, PubMed, Applied Social Sciences Index and Abstracts (ASSIA) and Web of Science. Of the 638 articles identified from 2010 to June 2021, 32 were selected for data extraction. The authors evaluated the risk of bias and quality of evidence of the studies included using the Mixed Methods Appraisal Tool. Main themes categorized include 7 dimensions of psychosocial risk factors: work intensity and working hours; emotional demands; autonomy; social relationships at work; conflict of values, work insecurity and home/work interface. Results The results revealed scant practice of full-time teleworking prior to the pandemic. Regarding the psychosocial risk factors found, differences were evident before and during the COVID-19 pandemic. For part-time and full-time telework prior to the pandemic, the dimensions of intensification of work and working hours, social relationships at work, and the home-work interface were the most prominent factors. However, studies performed during the COVID-19 pandemic where teleworking was mostly performed full-time, there was an increase in focus on emotional demands and the home-work interface, and a reduction in the other dimensions. Discussion Full-time telework brings important changes in working conditions and has the potential to affect living and health conditions of teleworkers. Part-time teleworking may have positive impact on psychosocial risk factors, favoring work-home balance, communication, and social relationships. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=191455, PROSPERO 2020 CRD4202019 1455.